The Cerebral Palsy Kinematic Assessment Tool (CPKAT): feasibility testing of a new portable tool for the objective evaluation of upper limb kinematics in children with cerebral palsy in the non-laboratory setting. (18th May 2016) - Preston, Nick; Weightman, Andrew; Culmer, Peter; Levesley, Martin; Bhakta, Bipin; Mon-Williams, Mark
Abstract: Purpose : Efficacy of treatment to improve upper-limb activity of children with cerebral palsy (CP) is typically evaluated outside clinical/laboratory environments through functional outcome measures (e.g. ABILHAND kids). This study evaluates CPKAT, a new portable laptop-based tool designed to objectively measure upper-limb kinematics in children with CP. Methods : Seven children with unilateral CP (2 females; mean age 10 years 2 months (SD 2 years 3 months), median age 9 years 6 months, range 6 years 5 months, MACS II–IV) were evaluated on copying, tracking and tracing tasks at their homes using CPKAT. CPKAT recorded parameters relating to spatiotemporal hand movement: path length, movement time, smoothness, path accuracy and root mean square error. The Wilcoxon signed ranks test explored whether CPKAT could detect differences between the affected and less-affected limb. Results : CPKAT detected intra-limb differences for movement time and smoothness (aiming), and path length (tracing). No intra-limb tracking differences were found, as hypothesised. These findings are consistent with other studies showing that movements of the impaired upper limb in unilateral CP are slower and less smooth. Conclusion : CPKAT provides a potential solution for home-based assessment of upper limb kinematics in children with CP to supplement other measures and assess functional intervention outcomes. Further validation is required. Implications for Rehabilitation: This paper demonstrates the feasibility of evaluating upper limb kinematics in home using CPKAT, a portable laptop-based evaluation tool. We found that CPKAT is easy to set-up and use in home environments and yields useful kinematic measures of upper limb function. CPKAT can complement less responsive patient reported or subjectively evaluated functional measures for a more complete evaluation of children with cerebral palsy. Thus, CPKAT can help guide a multi-disciplinary team to more effective intervention and rehabilitation for children with cerebral palsy.